2015
DOI: 10.1007/s10535-014-0470-1
|View full text |Cite
|
Sign up to set email alerts
|

Glucose application protects chloroplast ultrastructure in heat-stressed cucumber leaves through modifying antioxidant enzyme activity

Abstract: To elucidate a physiological mechanism of heat stress mitigation by exogenous glucose, seedlings of Cucumis sativus cv. Jinchun No. 4 were pretreated with glucose and then exposed to normal (25/18 °C) and elevated (42/38 °C) temperatures. We investigated whether glucose can protect cucumber plantlets and chloroplast ultrastructure from heat and whether this protection is associated with antioxidant enzymes, proline, and soluble sugars. Heat inhibited plant growth, disorganized membranes of 86.33 % of chloropla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 44 publications
0
19
0
3
Order By: Relevance
“…Huang et al . 19 found that glucose application increases the transcriptions of some antioxidant enzymes under heat stress. The up-regulation of these genes contributed to an enhanced adaptation to high temperature stress in cucumber roots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang et al . 19 found that glucose application increases the transcriptions of some antioxidant enzymes under heat stress. The up-regulation of these genes contributed to an enhanced adaptation to high temperature stress in cucumber roots.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are scavenged by plant antioxidant defense systems which include non-enzymatic antioxidants (such as ascorbic acid, AsA; glutathione, GSH) and antioxidant enzymes (such as superoxide dismutase, SOD; catalase, CAT; ascorbate peroxidase, APX; glutathione reductase, GR; guaiacol peroxidase, G-POD) 16 17 . Proline accumulation has been reported during various stress conditions, including drought 18 and heat 19 . Proline is important in cellular homeostasis (cell proliferation or cell death) and can act as a signaling molecule to modulate mitochondrial functions and trigger specific genes expression, which is essential for plant recovery from stresses 20 .…”
mentioning
confidence: 99%
“…In comparison, proline contents and POD activity improved in plants previously in vitro cultured in media with 30 g L -1 sucrose and GA 3 , which can be related to drought tolerance of these plants. Studies show that exogenous glucose application enhances tolerance of plants to dehydration and heat stress by increasing the content of proline and activities of antioxidants and repressing ROS accumulation (Huang et al, 2013(Huang et al, , 2015Cao et al, 2015), corroborating this hypothesis. There were no differences in enzymatic activity between the materials submitted to dehydration and the control after rehydration, suggesting a high adaptability of this species to water stress conditions and recovery after the end of stress period.…”
Section: Discussionmentioning
confidence: 52%
“…The chloroplast, a unique plant organelle, is the site of photosynthesis, intracellular signaling, and the production of various compounds important in metabolism, such as amino acids, hormones, nucleotides, vitamins, lipids, and secondary metabolites [ 7 , 8 , 9 ]. Chloroplasts also serve as sensors of the external environment.…”
Section: Introductionmentioning
confidence: 99%